Teaching Performance Assessment and the Student's Academic Achievement - Estiningtyas, Estiningtyas; Christiana Arin Proborini (Jurnal Ilmiah Kesehatan Mandira Cendikia, 2024)
Student achievement has focused on several empirical studies to measure the education output by examining the student performance measured by the standardised test and school resources characteristic concerning educational quality. Teacher performance assessment is a vital aspect of the learning process that directly affects students' knowledge attainment. This study aimed to analyse the difference between the teaching performance assessment and students' academic performance. The design used was an observational analytic study with a cross-sectional approach. The population of the study is the Level 1 Nursing Students at Mitra Husada Health College. The sampling techniques used were total sampling, resulting in 53 respondents. The instrument used was the Teaching Performance Assessment rubrics filled by the students and the final exam scores. The Kolmogorov-Smirnov and Kruskal Wallis were deployed to analyse the data. The study results show that the difference in teaching performance assessment is not associated with students' academic achievements. Teaching performance assessment does not contribute to cognitive outcomes but may significantly impact non-cognitive outcomes. The level of the exam affects the test scores. Teachers and policymakers should rely on more than just the cognitive effects measured by test scores. However, teacher performance may have a high impact on the skill and attitude development of the students.